Emergency Department Visits for Behavioral Health Concerns After Sexual Assault: A Retrospective Mixed Methods Study. Issue 12 (December 2021) - Robinson, Elizabeth; Ketterer, Tara; Molnar, Jennifer; DiGirolamo, Sara; Rockey, Alison; Brennan, Brian; Lavelle, Jane; Mollen, Cynthia
Abstract : N/A: The mental health issues that can follow sexual assault are well described. Mental health service (MHS) referrals can be beneficial but can be challenging to obtain. Absence of MHS can exacerbate mental health issues and lead to subsequent emergency visits. Sexual assault victims may therefore have an increased risk of returning to the emergency department (ED). Objectives: The primary purpose of this study was to identify the prevalence of patients who are victims of sexual assault who subsequently return to the ED with behavioral health (BH) concerns. The secondary purpose of this study was to explore potential factors that may affect whether a patient returns to the ED. Methods: Using a retrospective design, we examined electronic medical records and a quality improvement database of patients aged 12 to 15 years (inclusive) who sought care in a large, urban, freestanding, tertiary care children's hospital ED after an acute sexual assault. Results: Our primary finding was that of 192 included patients, 24.5% (95% confidence interval, 18.6%–31.2%) subsequently returned to the ED with BH concerns. Of these, 14 (7.3%) returned within 6 months. Secondary aim results included observed trust and mistrust in providers as documented in ED provider notes among patients with previous experience in the MHS system. Conclusions: A substantial proportion of patients who are victims of sexual assault return to the ED for BH concerns at some point. Further investigation is needed to determine factors affecting a return visit to the ED, which can lead to improved services when caring for sexual assault victims.